The Technology of Developing Media Culture in Higher Educational Students - Ruzieva, Dilnoz Isomjanovna; Rustamova, Nodira Rustamovna; Tursunov, Diyor Sunnatovich; Khurramov, Anvar Jumanazarovich (International Journal of Psychosocial Rehabilitation, 2020)
This article is written about the result of research on the development of technology for the development of media culture of students of higher educational institutions. The aim of the research is development of media culture of higher educational institution students, and the object of the research development of media culture of higher educational institution students. The tasks of the research are following from analysis of the condition of the technology to develop media culture in students of secondary educational institutions; defining of the educational process of developing media culture in students of secondary education institutions based on media culture development technologies employed abroad; improving the mechanism and content of media culture development in higher educational institution students; suggesting recommendations on expansion of pedagogical opportunities of media culture development in higher educational institution students. The article consists of from introduction, literature survey, methodology, recommendation, discussions, and conclusion.